THE DESIGN OF EXPERT SYSTEM APPLICATION FOR DIAGNOSING AUTISM DISORDERS IN CHILDREN - Indyah Hartami Santi (Universitas Islam Balitar, 2019)
The level of public understanding of autistic disorders and how to handle them that still lacking is the main reason in this study. How to know that a child has an autistic disorder or not is generally done by manual and simple way, it done by filling out a checklist or questionnaire that contains facts, attitudes and behaviors that often appear in children. The checklist is filled by parents who will then be observed again by the therapist to get clear, accurate, and reliable results. The weakness from this method in diagnosing there is an autistic disorder or not is it must involve therapists/experts who are currently still few in number. The purpose of this study is to make a software namely an expert system application that able to diagnose autistic disorders in children that are tailored to the needs of parents. The results of this study are a series of product design systems for expert systems to diagnose autistic disorders in children including ongoing system flowcharts, computerized system flowcharts, Data Flow Diagrams, application program flowcharts and display of application programs that have been built. The results of designing expert system software applications are expected to be used by therapists in diagnosing children who come to consult